2020
DOI: 10.1016/s0140-6736(20)31356-8
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pandemic and admission rates for and management of acute coronary syndromes in England

Abstract: Summary Background Several countries affected by the COVID-19 pandemic have reported a substantial drop in the number of patients attending the emergency department with acute coronary syndromes and a reduced number of cardiac procedures. We aimed to understand the scale, nature, and duration of changes to admissions for different types of acute coronary syndrome in England and to evaluate whether in-hospital management of patients has been affected as a result of the COVID-19 pandemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

61
675
14
19

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 599 publications
(769 citation statements)
references
References 15 publications
61
675
14
19
Order By: Relevance
“…Even though primary percutaneous coronary intervention is recommended as the treatment of choice for patients with STEMI, 4 we observed a large decline in catheterization laboratory activation during the pre-lockdown and lockdown periods as most of the patients either presented late or the treating physician opted for thrombolysis. A recently published analysis from the UK did not show an overall increase in inhospital mortality, 5 however inhospital mortality rates in our study increased to 7.27% in the lockdown period compared with 2.79% in the pre-COVID period. An increase in ischaemic time due to a lack of or delayed reperfusion therapy and selective referral of patients with myocardial infarction related complications appears to have resulted in increased mortality rates in patients admitted during the prelockdown and lockdown periods, with the worst prognosis in patients presenting during lockdown.…”
Section: Discussioncontrasting
confidence: 91%
“…Even though primary percutaneous coronary intervention is recommended as the treatment of choice for patients with STEMI, 4 we observed a large decline in catheterization laboratory activation during the pre-lockdown and lockdown periods as most of the patients either presented late or the treating physician opted for thrombolysis. A recently published analysis from the UK did not show an overall increase in inhospital mortality, 5 however inhospital mortality rates in our study increased to 7.27% in the lockdown period compared with 2.79% in the pre-COVID period. An increase in ischaemic time due to a lack of or delayed reperfusion therapy and selective referral of patients with myocardial infarction related complications appears to have resulted in increased mortality rates in patients admitted during the prelockdown and lockdown periods, with the worst prognosis in patients presenting during lockdown.…”
Section: Discussioncontrasting
confidence: 91%
“…Numerous international studies have reported the decline in hospital presentations for a range of CV emergencies. [6][7][8][9][10][11] To the best of our knowledge, this is the first study to show that this is associated with an adverse overall CV impact. While stroke and acute coronary syndrome accounted for the vast majority of acute CV deaths, the number of deaths in hospital due to these conditions fell below that expected for the time of year and it increased in the community, and particularly in people's homes.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] Yet, we and others have shown a substantial reduction in presentations to hospitals with acute cardiovascular (CV) conditions including acute coronary syndrome, heart failure, cardiac arrhythmia and stroke during the pandemic. [6][7][8][9][10][11] This would be expected to result in a much higher number of deaths, unless there has been an actual decrease in the incidence of these acute conditions. The detailed impact on mortality from acute CVD has, however, not been studied at national level.…”
Section: Introductionmentioning
confidence: 99%
“…2 3 Recent reports indicate that fewer patients present to hospitals with myocardial infarction (MI) while the incidence of cardiac arrest have increased in hard-hit areas, raising the question if fear of acquiring COVID-19 results in healthcare avoidance with consequent higher cardiac-related mortality. [4][5][6][7][8][9] However, most reports have either been anecdotal, survey results or geographically limited to areas with lockdowns as a mean of regressing disease transmission. We examined the incidence of MI during the ongoing COVID-19 pandemic in Sweden, which remained an open society with a different public health approach fighting COVID-19.…”
Section: Original Researchmentioning
confidence: 99%